Rancang Bangun Aplikasi Elektronik Resep yang Terhubung ke Kasir Menggunakan Website - Helfy Susilawati; Tri Arif Wiharso; Teddy Mulyadi Hidayat (Jurnal Teknologi Informasi dan Terapan, 2020)
A recipe is a description given by a doctor about a medicine and its dosage. Currently the recipes used are still using manual recipes that are written by hand. The most common weakness of manual recipes is the handwritten recipe which is difficult to understand. Most of the patients do not understand the doctor's writing, except the pharmacist . An electronic recipe is a recipe given by a doctor in the printed recipe of a recommended medicine. The purpose of electronic recipe is the recipe can be read clearly by the patient and also by the pharmacist. In addition, electronic recipe can also make it easier for patients to pay for medicines at the cashier. If in manual procedures the patient has to queue 2 times at the checkout, using an electronic prescription, the patient only needs to queue once at the cashier, which is when paying for medicine only. The method used in this research is the Prototype method, and using website for its interface. From this research, the results show that the application built on the website is 100% well run and usable. This is obtained from the results of 30 respondents who tried the application.